AXBOROT XAVFSIZLIGI SOHASIDA LOYIHALASHTIRISH KOMPETENSIYALARINI RIVOJLANTIRISH METODIKASI - Anvar Kutlimuratov, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article highlights the methodological foundations for the development of design competencies in the field of information security. The theoretical foundations, methods, and technologies for the formation of design competencies are analyzed. Modern technologies used for the development of design competencies in the educational process are also considered. The article proves the effectiveness of the methodology based on experimental studies and provides relevant recommendations.